2016
DOI: 10.1095/biolreprod.116.144337
|View full text |Cite
|
Sign up to set email alerts
|

Signaling mechanisms in mammalian sperm motility<sup><xref ref-type="fn" rid="afn1">†</xref></sup>

Abstract: The goal of sperm is to fertilize the oocyte. To achieve that purpose, it must acquire motility in the epididymis and hyperactivated motility in the female reproductive tract. Motility is only achieved when the sperm presents a fully functional flagellum, is capable of producing energy to fuel the movement, and suffers epididymal maturation and capacitation. Since sperm is a transcriptionally silent cell, motility depends on the activation and/or inhibitions of key signaling pathways. This review describes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 124 publications
0
28
0
Order By: Relevance
“…To acquire progressive motility and fertility competence, sperm need to undergo two post-testicular maturation processes, i.e. the one occurring in the male epididymis is known as epididymal sperm maturation and the other is designated as capacitation expressed in the female reproductive tract ( Freitas et al, 2017 ). On the other hand, both of these changes are associated with sequential biochemical changes occurring in different sperm segments ( Freitas et al, 2017 ; Gervasi and Visconti, 2017 ; Puga Molina et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…To acquire progressive motility and fertility competence, sperm need to undergo two post-testicular maturation processes, i.e. the one occurring in the male epididymis is known as epididymal sperm maturation and the other is designated as capacitation expressed in the female reproductive tract ( Freitas et al, 2017 ). On the other hand, both of these changes are associated with sequential biochemical changes occurring in different sperm segments ( Freitas et al, 2017 ; Gervasi and Visconti, 2017 ; Puga Molina et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…These signaling enzymes, protein phosphatase 1 (PP1), glycogen synthase kinase 3 (GSK3) and the calcium activated phosphatase (PP2B), affect sperm function in the epididymis and in the female reproductive tract. Several reviews detail the roles of sperm cAMP-PKA and calcium metabolism (Visconti et al, 2002;Burton and McKnight, 2007;Buffone et al, 2014;Stival et al, 2016;Freitas et al, 2017;Balbach et al, 2018;Leemans et al, 2019;Stewart and Davis, 2019). Following a brief summary of the actions of cAMP-PKA, calcium and pH, the remainder of the review will be focused largely devoted to examination of the key roles of PP1, GSK3, and calcium activated protein phosphatase, PP2B (PPP3R2/CC) in mediating the actions of the second messengers during sperm maturation and fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were no significant differences in the phosphorylation levels at the phosphotyrosine site (Y623) of FSIP2, this site was identified as a new phosphosite ( Supplementary Data 3 ); a previous study reported different sites (Y630, Y1635, Y6101, and Y6351) [ 16 ]. In the sperm principal piece, the fibrous sheath supports signaling proteins that regulate motility, capacitation, and hyperactivation [ 29 ]. The major components of the sheath are AKAP3 and AKAP4, which probably form the integral cytoskeleton structure [ 30 ].…”
Section: Discussionmentioning
confidence: 99%